하악골 양측 하악지 시상분할 골절단술 후 흡수성 고정의 안정성에 관한 연구 - 최병환(Byoung-Hwan Choi); 박수원(Su-Won Park); 장수미(Soo-Mi Jang); 손한나(Han-Na Son); 박봉찬(Bong-Chan Park); 손장호(Jang-Ho Son); 조영철(Yeong-Cheol Cho); 성일용(Iel-Yong Sung) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2010)
Introduction: To evaluate the skeletal stability after a bilateral sagittal split osteotomy (BSSO) setback of the mandible fixed with a biodegradable internal fixation device or metal internal fixation device. Materials and Methods: Thirty consecutive patients underwent mandibular setback via BSSO. Fifteen patients were fixed with a biodegradable internal fixation device or metal internal fixation device respectively. Posteroanterior (PA) and lateral cephalograms were taken preoperatively and at two days, 5.5 months and 14.5 months postoperatively. The relevant skeletal points were traced and digitized to evaluate the skeletal changes postoperatively. The relapse rates were analyzed and compared statistically. Results: There was no statistically significant differences in postoperative stability between the two groups.(P<0.05)Conclusion: The biodegradable internal fixation device may make an effective device alternative to a metal internal fixation device for setback BSSO. KCI Citation Count: 0